Changes in the Width of the Tibiofibular Syndesmosis Related to Lower Extremity Joint Dynamics and Neuromuscular Coordination on Drop Landing During the Menstrual Cycle. Issue 9 (4th September 2017) - Okazaki, Michie; Kaneko, Masaaki; Ishida, Yukisato; Murase, Norio; Katsumura, Toshihito
Background: Many injuries of the lower extremities, especially the knee and ankle, occur during sports activity, and the incidence rate is higher in women than in men. Hypothesis: The hypothesis was that phases of the menstrual cycle affect the width of the tibiofibular syndesmosis during drop landing in healthy young women and that such changes at the tibiofibular joint also affect the dynamics and neuromuscular coordination of the lower extremities. Study Design: Descriptive laboratory study. Methods: Participants included 28 healthy young women (mean age, 21.0 ± 0.8 years). Blood samples were collected to determine plasma levels of estradiol and progesterone immediately before the performance of the task: drop landing on a single leg from a 30-cm platform. Using ultrasonography, the distance between the tibia and the distal end of the fibula, regarded as the width of the tibiofibular syndesmosis, was measured in an upright position without flexion of the ankle. The peak ground-reaction force (GRF) on landing was measured using a force platform. The time to peak GRF (Tp-GRF) was measured as the time from initial ground contact to the peak GRF. Hip, knee, and ankle joint angles during the single-leg landing were calculated using a 3-dimensional motion analysis system. Muscle activities of the lower extremities were measured using surface electromyography. Results: The width of the tibiofibular syndesmosis was significantly greater in the luteal phase when compared with the menstrual, follicular, and ovulation phases (by 5%-8% of control). Also, during the luteal phase, the Tp-GRF was significantly shorter than in the follicular phase (by 6%); hip internal rotation and knee valgus were significantly greater than in the menstrual phase (by 43% and 34%, respectively); knee flexion was significantly less than in the menstrual and follicular phases (by 7%-9%); ankle dorsiflection was significantly less than in the follicular phase (by 11%); ankle adduction and eversion were significantly greater than in the menstrual and follicular phases (by 26%-46%, and 27%-33%, respectively); and activation of the gluteus maximus before landing was significantly lower than in the menstrual and follicular phases (by 20%-22%). Conclusion: The luteal phase appears to be associated with decreased strength and laxity of the ankle as well as lower extremity muscle activity in women. The changes presumably represent a greater risk for sports injuries. Clinical Relevance: The results of this study suggest that the luteal phase may be related to the greater incidence of lower extremity injuries in women.